2016
DOI: 10.3389/fncel.2016.00258
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Sphingosine 1-Phosphate Receptor Subtype 3 Impairs Hippocampal Neuron Excitability In vitro and Spatial Working Memory In vivo

Abstract: Understanding the role of the bioactive lipid mediator sphingosine 1-phosphate (S1P) within the central nervous system has recently gained more and more attention, as it has been connected to major diseases such as multiple sclerosis and Alzheimer's disease. Even though much data about the functions of the five S1P receptors has been collected for other organ systems, we still lack a complete understanding for their specific roles, in particular within the brain. Therefore, it was the aim of this study to furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…This is especially useful given that it was recently discovered that GPCRs display sequence selectivity for distinct G protein coupled pathways. 42 Their analysis revealed at least one S1P receptor, S1P 3 (the primary S1P receptor in the nervous system 6 , 43 ), was shown to display a uniquely promiscuous pattern of G protein coupling, which is supported by recent studies of S1P 3 signaling mechanisms in neurons 38 . Unlike our experiments using photoswitchable S1P, substitution of native receptors with a DREADD or a light-activated GPCR would not allow for mechanistic study of the endogenous S1P signaling pathways.…”
Section: Discussionmentioning
confidence: 80%
“…This is especially useful given that it was recently discovered that GPCRs display sequence selectivity for distinct G protein coupled pathways. 42 Their analysis revealed at least one S1P receptor, S1P 3 (the primary S1P receptor in the nervous system 6 , 43 ), was shown to display a uniquely promiscuous pattern of G protein coupling, which is supported by recent studies of S1P 3 signaling mechanisms in neurons 38 . Unlike our experiments using photoswitchable S1P, substitution of native receptors with a DREADD or a light-activated GPCR would not allow for mechanistic study of the endogenous S1P signaling pathways.…”
Section: Discussionmentioning
confidence: 80%
“…On hippocampal slices, it has been shown that S1PR1 signaling influences NMDAR properties [101]. Similarly, ablation of S1PR3 impairs neuronal hippocampal excitability in vitro [102] and reduces inflammatory processes in medial prefrontal cortex in mice [103], both areas involved in pain processing [104]. However, more in-depth studies on S1P signaling also need to be addressed towards other brain structures responsible for pain modulation, such as cingulate cortex, thalamus, periaqueductal grey, and rostroventral medulla.…”
Section: S1p Axis In Central Sensitizationmentioning
confidence: 99%
“…Sphingosine-1-phosphate receptor 3 is a G protein-coupled receptor that, upon binding to its ubiquitous ligand sphingosine-1-phosphate (S1P), plays a critical role in regulating multiple cellular processes including inflammation, migration, angiogenesis, differentiation, and proliferation in peripheral tissue 1219 . Little is known about the function of S1PR3 in the brain, although a role for S1PR3 in spatial working memory and excitability of hippocampal neurons in rodents has been reported 20 . In this study, we identify S1PR3 in the mPFC as a key mediator of resilience to the adverse effects of stress in rats.…”
Section: Introductionmentioning
confidence: 99%